ROS-responsive exogenous functional mitochondria can rescue neural cells post-ischemic stroke - Li, Yanjiao; Wang, Yachao; Yang, Weiqi; Wu, Zhen; Ma, Daiping; Sun, Jianxiu; Tao, Huixian; Ye, Qinlian; Liu, Jingnan; Ma, Zhaoxia; Qiu, Lihua; Li, Weiping; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: The transfer of mitochondria from healthy mesenchymal stem cells (MSCs) to injured MSCs has been shown to have potential therapeutic benefits for neural cell post-ischemic stroke. Specifically, functional mitochondria can perform their normal functions after being internalized by stressed cells, leading to host cell survival. However, while this approach shows promise, there is still a lack of understanding regarding which neural cells can internalize functional mitochondria and the regulatory mechanisms involved. To address this gap, we investigated the ability of different neural cells to internalize exogenous functional mitochondria extracted from MSCs. Methods: Functional mitochondria (F-Mito) isolated from umbilical cord derived-MSCs (UCMSCs) were labeled with lentivirus of HBLV-mito-dsred-Null-PURO vector. The ability of stressed cells to internalize F-Mito was analyzed using a mouse (C57BL/6J) middle cerebral artery occlusion (MCAO) model and an oxygen-glucose deprivation/reoxygenation (OGD/R) cell model. The cell viability was measured by CCK-8 kit. Time-course of intracellular ROS levels in stressed cells were analyzed by DCFH-DA staining after OGD/R and F-Mito treatment. MitoSOX, Mitotracker and WGA labeling were used to assess the relationship between ROS levels and the uptake of F-Mito at the single-cell level. Pharmacological modulation of ROS was performed using acetylcysteine (ROS inhibitor). Results: Our findings demonstrate that neurons and endothelial cells are more effective at internalizing mitochondria than astrocytes, both in vitro and in vivo, using an ischemia-reperfusion model. Additionally, internalized F-Mito decreases host cell reactive oxygen species (ROS) levels and rescues survival. Importantly, we found that the ROS response in stressed cells after ischemia is a crucial determinant in positively mediating the internalization of F-Mito by host cells, and inhibiting the generation of ROS chemicals in host cells may decrease the internalization of F-Mito. These results offer insight into how exogenous mitochondria rescue neural cells via ROS response in an ischemic stroke model. Overall, our study provides solid evidence for the translational application of MSC-derived mitochondria as a promising treatment for ischemic stroke.